A Study on Application-layer Attacks in Communications Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Distributed Denial of Service(DDoS) attacks are now a threat to Internet. Though traditionallyDDoS attacks stuck at network layer, recently an increasing number of DDoS attacks occur atapplication layer. They target specific web applications. These attacks appear as legitimatetraffic, because of their low and slow rate. In this paper, we introduce DDoS attacks along withtaxonomy and method to detect application layer DDoS(App-DDoS) attacks. Recent researchtrends in application-layer attack detection are also included